The importance of teamwork in libraries / Hajah Norsham Muslim - Muslim, Norsham (1999)
A Changing Environment Issues that affect academic libraries from mid 198O's till today a External environment a Lower levels of budgetary support from government • Sky - rocking inflation in serials industry a The value of the dollar/ringgit on world market • Automation was an accomplised goal for large libraries but managers not happy with the quality and level of access that early system provide • Students more assertive in demands for improved services • Faculty more outspoken about their needs from the library.